2013
DOI: 10.1007/s12010-013-0562-y
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Production by Bacillus megaterium: Effect of Growth Phase and Cultural Conditions

Abstract: Siderophore production by Bacillus megaterium was detected, in an iron-deficient culture medium, during the exponential growth phase, prior to the sporulation, in the presence of glucose; these results suggested that the onset of siderophore production did not require glucose depletion and was not related with the sporulation. The siderophore production by B. megaterium was affected by the carbon source used. The growth on glycerol promoted the very high siderophore production (1,182 μmol g(-1) dry weight biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…Given the lack of B vitamins in a blood diet, it is possible that triatomines obtain these nutrients from Bacillus megaterium (Baines, 1956). Transport and assimilation of iron are other possible functions for this microorganism, since solubilization agents for iron have been shown to be produced by B. megaterium (Santos et al, 2014). Therefore, it is unsurprising that previous studies have proposed B. megaterium for its use in paratransgenic studies of sand flies (which are vectors of Leishmaniasis) (Hillesland et al, 2008;Mukhopadhyay et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of B vitamins in a blood diet, it is possible that triatomines obtain these nutrients from Bacillus megaterium (Baines, 1956). Transport and assimilation of iron are other possible functions for this microorganism, since solubilization agents for iron have been shown to be produced by B. megaterium (Santos et al, 2014). Therefore, it is unsurprising that previous studies have proposed B. megaterium for its use in paratransgenic studies of sand flies (which are vectors of Leishmaniasis) (Hillesland et al, 2008;Mukhopadhyay et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The medium used in this work included MKB medium [6]; Arginine medium [7] (AM); Luria-Bertani (LB) medium [8]; Czapek Dox medium [8]; CAS [9] solution; AM was modified by replacing glucose of arginine medium with 20 g/L glycerol along with the reduction of arginine to 1 g/L.…”
Section: Media and Culture Conditionmentioning
confidence: 99%
“…In order to verify whether carbon source [7] and amino acid [7] had an influence on siderophore unit and growth of MB8, xylose, maltose, lactose, soluble starch, sucrose, fructose, and glycerol were used as an alternative carbon source to glucose in AM. Moreover, arginine was replaced with alanine, cysteine, aspartic acid, histidine, glutamate, glutamine, and glycine, respectively, to investigate the amino acid effect on siderophore production.…”
Section: The Effect Of Fermentation Parametersmentioning
confidence: 99%
“…We used glucose broth medium for cultivation the microorganisms in order to estimate the siderophores production since it has recently been shown that using glucose as carbon source in the culture medium could enhance the siderophore production compared to other carbon sources such as lactose and maltose (Santos et al, 2014). On the other hand, it was found that the effect of the carbon source on the siderophore production differ according to the type of the microorganisms (Chincholkar et al, 2007).…”
Section: Factors Influencing the Siderophore Production By The Isolatmentioning
confidence: 99%
“…The aerobic conditions as we used in our study commonly results in a high production of siderophores. The involvement of aerobic metabolism in the production of siderophores is necessary for a high yield of siderophores, since the absence of aeration does not prevent siderophore production but it strongly decreases the concentration (Santos et al, 2014). Siderophores production could also vary according to the time of cultivation.…”
Section: Factors Influencing the Siderophore Production By The Isolatmentioning
confidence: 99%